Interfacial Enhanced 1D–2D Composite toward Mechanically Robust Strain Sensors. Issue 30 (9th September 2022) - Shang, Kedong; Yang, Tingting; Guo, Chuanfei; Pu, Xiaobo; Zhang, Yong; Lu, Xulei; He, Changliu; Zhou, Jian; Wu, Lei; Yu, Bingjun; Jiang, Liang; Qian, Linmao
Abstract: Flexible sensors with the ability to precisely detect the full range of tiny strain (less than 0.1%), small strain (within 1%), and large strain (≈50%) are in significant demand to satisfy the requirements for electronic skin applications. More importantly, the sensor performance is required to be accurate and reliable when operating in some unconstrained environments, such as excessive extension, high bending, torsion, and scratching impact. However, it remains challenging to meet all these requirements simultaneously in a single strain sensor. Herein, an ultrathin composite film composed of reduced oxide (rGO) and carbon tube (CNT) is prepared, and then transferred onto a modified elastomer polydimethylsiloxane surface that forms strong hydrogen bond interaction with the film. The as‐fabricated sensor achieves wide range and high sensitivity (gauge factor (GF) ≈ 105, 160, and 310 in the strain regions of 0–25%, 25–40%, and 40–50%, respectively). More importantly, the proposed strain sensor performs mechanical robustness, low hysteresis, scratch resistance due to the effective improvement of interfacial slipping and delamination. The sensor can be used to monitor human physiological information, including pulse waveforms in a variety of wrist postures and acoustic vibration signal (≈7 kHz). Abstract : A strain sensor design strategy that adopts 1D (rGO)–2D (CNT) composite structure and strong interfacial bonding with elastic substrate (PDMS) is proposed. The sensors possess both high basic performance (high strain sensitivity and large stretching) and high mechanical robustness (adaptation to overstretching, bending and torsion, low hysteresis, and scratch‐resistance).